Efficacy and safety of endoscopic stent placement for afferent loop obstruction using a short double‐balloon endoscopy - Takashi Ito; Masaaki Shimatani; Masataka Masuda; Koh Nakamaru; Toshiyuki Mitsuyama; Norimasa Fukata; Tsukasa Ikeura; Makoto Takaoka; Kazuichi Okazaki; Makoto Naganuma (DEN Open)
Abstract Background Afferent loop obstruction (ALO) is a rare mechanical complication that occurs after gastrojejunostomy. Recently the use of double‐balloon endoscopy (DBE) can be useful for benign and malignant ALO. Methods We retrospectively identified 22 patients who underwent DBE for ALO from January 2009 to December 2020. We evaluated the efficacy and safety of short DBE treatment for ALO. Results Short DBE was able to reach an obstructive site in the afferent limb in all patients (100%) and was able to reach the blind end in 14 patients (64%). The technical success rate was 100%, and the clinical success rate was 95%. Procedure‐related adverse events occurred in two patients (9%). In the case of benign ALO, three of nine patients showed improvement in ALO with single stent placement. Two of nine patients improved after the replacement of the plastic stent (PS) two or three times. Four of nine patients continued with the replacement of PS. In the case of malignant ALO, the metallic stent was placed in 10 patients, and eight patients with metallic stents did not experience stent occlusion until they died. Reintervention was attempted in six patients (27%) with benign ALO but was not attempted in malignant ALO. Conclusions Treatments for ALO using the short DBE was effective and relatively safe because the technical and clinical success rates were very high and there were relatively low complications. Consequently, short DBE could be the first‐choice treatment for both benign and malignant ALO.